2022
DOI: 10.1111/cen.14860
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of Graves' disease during the SARS‐CoV2 pandemic

Abstract: Introduction COVID‐19 has a wide spectrum of clinical severity and there is evidence that SARS‐Cov2 affects several organs and systems. Among the organs affected since the beginning of the pandemic, the relationship between SARS‐CoV‐2 infection and thyroid involvement has been demonstrated. Novel and highly effective messenger RNA and DNA‐based vaccines have been rapidly developed to decrease SARS‐CoV‐2 morbidity and mortality. Early after mass vaccinations, cases of thyroid dysfunction mainly inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…During the SARS-CoV-2 (COVID-19) pandemic, cases of Graves disease and subacute thyroiditis related to COVID-19 infection or vaccination were reported, presumably due to the immunogenic nature of COVID-19 . A retrospective study reported a 2-fold increase in the incidence of Graves disease in a Spanish hospital in 2020-2021 compared with the pre–COVID-19 years (2017-2019) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the SARS-CoV-2 (COVID-19) pandemic, cases of Graves disease and subacute thyroiditis related to COVID-19 infection or vaccination were reported, presumably due to the immunogenic nature of COVID-19 . A retrospective study reported a 2-fold increase in the incidence of Graves disease in a Spanish hospital in 2020-2021 compared with the pre–COVID-19 years (2017-2019) …”
Section: Methodsmentioning
confidence: 99%
“…[18][19][20] A retrospective study reported a 2-fold increase in the incidence of Graves disease in a Spanish hospital in 2020-2021 compared with the pre-COVID-19 years (2017-2019). 21…”
Section: Covid-19 and Hyperthyroidismmentioning
confidence: 99%
“…Under such circumstances, although the COVID-19 mRNA vaccine was developed and administered worldwide, various adverse effects have been reported, including cardiovascular diseases such as acute coronary syndrome (ACS) and myocarditis [ 2 , 3 , 4 ], and hyperthyroidism including Graves’ disease, Graves’ orbitopathy, subacute thyroiditis, and silent thyroiditis [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Expected cases of Graves’ disease in 2021 increased markedly compared to 2017–2019. Two-thirds of patients had a history of vaccination in the 90 days prior to symptom onset [ 11 ]. In healthcare workers, a gradual increase in the mean thyroid-stimulating hormone (TSH) receptor antibody (TRAb) in response to frequent vaccination has been reported [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation